The Influence of Leadership and Apparatus Competence on Public Service Effectiveness: The Mediating Role of Apparatus Job Satisfaction in Hatuquessi Suco, Liquiçá Municipality, Timor-Leste - Rosario dos Santos; Dhani Ichsanuddin Nur; Hesty Prima Rini (Asian Journal of Economics, Business and Accounting, 2026)
Aims: This study aims to examine the influence of Suco Head leadership and apparatus competence on public service effectiveness, with apparatus job satisfaction as a mediating variable in Suco Hatuquessi, Município Liquiçá, Timor-Leste. Study Design: This study employed a quantitative explanatory research design. Place and Duration of Study: The study was conducted in Suco Hatuquessi, Município Liquiçá, Timor-Leste, during 2026. Methodology: Data were collected through questionnaires using a Likert scale from respondents involved in the provision and receipt of public services in Suco Hatuquessi. The data were analysed using Partial Least Squares–Structural Equation Modelling (PLS-SEM) with SmartPLS 4. The analysis included the evaluation of the measurement model and structural model, as well as direct and indirect effect testing. Results: The findings indicate that Suco Head leadership does not have a significant direct influence on public service effectiveness (β = 0.016; P = .906). Apparatus competence also does not have a significant direct influence on public service effectiveness (β = 0.208; P = .157). However, Suco Head leadership has a positive and significant influence on apparatus job satisfaction (β = 0.252; P = .032), while apparatus competence has a positive and significant influence on apparatus job satisfaction (β = 0.411; P < .001). Apparatus job satisfaction has a positive and significant influence on public service effectiveness (β = 0.348; P = .006). The mediation analysis shows that apparatus job satisfaction does not significantly mediate the relationship between Suco Head leadership and public service effectiveness (β = 0.088; P = .096), but significantly mediates the relationship between apparatus competence and public service effectiveness (β = 0.143; P = .032). Conclusion: The findings demonstrate that leadership and apparatus competence do not directly determine public service effectiveness in Suco Hatuquessi. However, both contribute to apparatus job satisfaction, which plays an important role in strengthening public service effectiveness. In particular, apparatus job satisfaction serves as a significant mediating mechanism in the relationship between apparatus competence and public service effectiveness.